2021
DOI: 10.3390/ani11092498
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Recovery of the Fecal Microbiome and Metabolome of Dogs with Steroid-Responsive Enteropathy

Abstract: The long-term impact of treatment of dogs with steroid-responsive enteropathy (SRE) on the fecal microbiome and metabolome has not been investigated. Therefore, this study aimed to evaluate the fecal microbiome and metabolome of dogs with SRE before, during, and following treatment with standard immunosuppressive therapy and an elimination diet. We retrospectively selected samples from 9 dogs with SRE enrolled in a previous clinical trial, which received treatment for 8 weeks, and had achieved remission as ind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 58 publications
6
10
0
Order By: Relevance
“…In dogs, preliminary studies would suggest that the microbiota may normalize after dietary (eg, normalization of C hiranonis ) 39 or immunosuppressive therapy. 40 Whether the feline DI could act as a monitoring biomarker, a prognostic biomarker or a predictive biomarker requires further investigations in prospective clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…In dogs, preliminary studies would suggest that the microbiota may normalize after dietary (eg, normalization of C hiranonis ) 39 or immunosuppressive therapy. 40 Whether the feline DI could act as a monitoring biomarker, a prognostic biomarker or a predictive biomarker requires further investigations in prospective clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…30 Enterobacteriaceae are Gram-facultative aerobic bacteria that can exacerbate inflammation. 31 In contrast, Fusobacteria are more representative of healthy microbiome in dogs and their decrement is associated with chronic enteropathies. 31 The inconsistency of this result with a clear clinical improvement still needs clarification and further studies.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, there was also a significant increase in Enterococcaceae and Enterobacteriaceae , while Fusobacteriaceae were more abundant in the group of healthy dogs 30 . Enterobacteriaceae are Gram‐facultative aerobic bacteria that can exacerbate inflammation 31 …”
Section: Discussionmentioning
confidence: 99%
“…One study in mice showed that cobalamin supplementation was associated with significantly altered beta diversity but not alpha diversity [ 20 ], whereas beta diversity was unaffected in three other studies in mice [ 17 , 21 , 22 ]. At the genus level, an abundance of Bacteroides has been reported to decrease with oral supplementation with cyanocobalamin [ 20 ], a concerning finding since Bacteroides is commonly already decreased in dogs with CE and expected to improve with treatment [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%